Vejrforholdene i Landbrugsaaret 1945—46. (Fra 1. Oktober 1945 til 30. September 1946). - Hansen, H. (Tidsskrift for Landøkonomi, 2018)
Vejrforholdene i Landbrugsaaret 1945—46. (Fra 1. Oktober 1945 til 30. September 1946).